part 3. Find the value of the trig function indicated, use Pythagorean theorem to find the third side if you need it.
1 answer:
Answer: ![\bold{9)\ \sin \theta=\dfrac{1}{3}\qquad 10)\ \sin \theta = \dfrac{4}{5}\qquad 11)\ \cos \theta = \dfrac{\sqrt{11}}{6}\qquad 12)\ \tan \theta = \dfrac{17\sqrt2}{26}}](https://tex.z-dn.net/?f=%5Cbold%7B9%29%5C%20%5Csin%20%5Ctheta%3D%5Cdfrac%7B1%7D%7B3%7D%5Cqquad%2010%29%5C%20%5Csin%20%5Ctheta%20%3D%20%5Cdfrac%7B4%7D%7B5%7D%5Cqquad%2011%29%5C%20%5Ccos%20%5Ctheta%20%3D%20%5Cdfrac%7B%5Csqrt%7B11%7D%7D%7B6%7D%5Cqquad%2012%29%5C%20%5Ctan%20%5Ctheta%20%3D%20%5Cdfrac%7B17%5Csqrt2%7D%7B26%7D%7D)
<u>Step-by-step explanation:</u>
Pythagorean Theorem is: a² + b² = c² , <em>where "c" is the hypotenuse</em>
<em />
![9)\ \sin \theta=\dfrac{\text{side opposite of}\ \theta}{\text{hypotenuse of triangle}}=\dfrac{4}{12}\quad \rightarrow \large\boxed{\dfrac{1}{3}}](https://tex.z-dn.net/?f=9%29%5C%20%5Csin%20%5Ctheta%3D%5Cdfrac%7B%5Ctext%7Bside%20opposite%20of%7D%5C%20%5Ctheta%7D%7B%5Ctext%7Bhypotenuse%20of%20triangle%7D%7D%3D%5Cdfrac%7B4%7D%7B12%7D%5Cquad%20%5Crightarrow%20%5Clarge%5Cboxed%7B%5Cdfrac%7B1%7D%7B3%7D%7D)
Note: 4² + (8√2)² = hypotenuse² → hypotenuse = 12
![10)\ \sin \theta=\dfrac{\text{side opposite of}\ \theta}{\text{hypotenuse of triangle}}=\dfrac{16}{20}\quad \rightarrow \large\boxed{\dfrac{4}{5}}](https://tex.z-dn.net/?f=10%29%5C%20%5Csin%20%5Ctheta%3D%5Cdfrac%7B%5Ctext%7Bside%20opposite%20of%7D%5C%20%5Ctheta%7D%7B%5Ctext%7Bhypotenuse%20of%20triangle%7D%7D%3D%5Cdfrac%7B16%7D%7B20%7D%5Cquad%20%5Crightarrow%20%5Clarge%5Cboxed%7B%5Cdfrac%7B4%7D%7B5%7D%7D)
Note: 12² + opposite² = 20² → opposite = 16
![11)\ \cos \theta=\dfrac{\text{side adjacent to}\ \theta}{\text{hypotenuse of triangle}}=\dfrac{\sqrt{11}}{6}\quad =\large\boxed{\dfrac{\sqrt{11}}{6}}](https://tex.z-dn.net/?f=11%29%5C%20%5Ccos%20%5Ctheta%3D%5Cdfrac%7B%5Ctext%7Bside%20adjacent%20to%7D%5C%20%5Ctheta%7D%7B%5Ctext%7Bhypotenuse%20of%20triangle%7D%7D%3D%5Cdfrac%7B%5Csqrt%7B11%7D%7D%7B6%7D%5Cquad%20%3D%5Clarge%5Cboxed%7B%5Cdfrac%7B%5Csqrt%7B11%7D%7D%7B6%7D%7D)
Note: adjacent² + 5² = 6² → adjacent = √11
![12)\ \tan \theta=\dfrac{\text{side opposite of}\ \theta}{\text{side adjacent to}\ \theta}=\dfrac{17}{13\sqrt2}\quad =\large\boxed{\dfrac{17\sqrt2}{26}}](https://tex.z-dn.net/?f=12%29%5C%20%5Ctan%20%5Ctheta%3D%5Cdfrac%7B%5Ctext%7Bside%20opposite%20of%7D%5C%20%5Ctheta%7D%7B%5Ctext%7Bside%20adjacent%20to%7D%5C%20%5Ctheta%7D%3D%5Cdfrac%7B17%7D%7B13%5Csqrt2%7D%5Cquad%20%3D%5Clarge%5Cboxed%7B%5Cdfrac%7B17%5Csqrt2%7D%7B26%7D%7D)
Note: adjacent² + 7² = (13√2)² → adjacent = 17
You might be interested in
Step-by-step explanation:
hsbsbs snz s nsnsnsssksnnsjs
Answer:
x = 21.3 repeating. so put the - on top of the 3 if you're writing it down
Answer:
25/14
Step-by-step explanation:
Answer:
![if \: your \: paradox \: is \: true \\ \: then \: you \: are \: wrong](https://tex.z-dn.net/?f=if%20%5C%3A%20your%20%5C%3A%20paradox%20%5C%3A%20is%20%5C%3A%20true%20%5C%5C%20%20%5C%3A%20then%20%5C%3A%20you%20%5C%3A%20are%20%5C%3A%20wrong)
Answer:
mean = 11.2 = 11
Step-by-step explanation:
mean = average = (10+11+10+12+10+11+13+13+11+11)/10 = 11.2=11